1995
DOI: 10.1007/bf02036561
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemical studies of the sorption behavior of strontium and barium

Abstract: The sorpt ion behavior of strontium and barium on kaolinite, bentonite and chlorite-illite mixed clay was studied by radi0mralytical techniques using file batch method. 90Sr (29.1 y) and 133Ba (10.5 y) were used as radiotracers. Characterization of the solid matrices was done by FFIR and XRD spectrometries and specific surface area measurements. Synthetic groundwater was used as the aqueous phase. The variation of the distribution ratio Rd, as a function of metal ion loading was examined. The sorption isotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, Erdal et al (1978) reported that pH does not have any major effect on Sr-sorption on granite. Gokturk et al (1995) also reported that no significant change in the sorption behavior of barium and strontium is observed between the pH range 3.0-8.5 for kaolinite and bentonite.…”
Section: Effect Of Ph On K Dmentioning
confidence: 94%
“…However, Erdal et al (1978) reported that pH does not have any major effect on Sr-sorption on granite. Gokturk et al (1995) also reported that no significant change in the sorption behavior of barium and strontium is observed between the pH range 3.0-8.5 for kaolinite and bentonite.…”
Section: Effect Of Ph On K Dmentioning
confidence: 94%
“…Many researchers have studied the removal of radionuclides from contaminated soil using different natural and artificial materials (Cho et al 1996;Göktürk et al 1995;IAEA 1995;Khan 2003;Lee et al 1997;Misra and Mehta 1995;Plećaš et al 1991;Shahwan and Erten 2001;Wang 2003). Bentonite was widely used as an adsorbent material by several researchers (Odom 1984;Montavon et al 2006;Murali and Mathur 2002;Göktürk et al 1995;Khan 2003;Lee et al 1997).…”
mentioning
confidence: 99%
“…Bentonite was widely used as an adsorbent material by several researchers (Odom 1984;Montavon et al 2006;Murali and Mathur 2002;Göktürk et al 1995;Khan 2003;Lee et al 1997). Bentonite has the ability to adsorb a large volume of water, 12-15 times the volume of dry state bentonite, thus forming a gel material.…”
mentioning
confidence: 99%